Dissolved gas analysis and fault diagnosis interface for oil-immersed transformer using fuzzy logic - (:unkn) unknown (Praise Worthy Prize, 2012)
In this study, the dissolved gases in oil due to the incipient failures in the oilimmersed transformer are analyzed and diagnosed by fuzzy logic approach considering the framework of IEC 60599 standard. In addition to the incipient failures of transformer, more precise results are obtained about the condition of cellulosic material by using CO2/CO rate. Fuzzy logic membership functions and rules designed to ensure compliance with the standards. For efficient use of this approach, a user friendly interface is created by using LabVIEW software package. The results obtained are compared with the results of diagnostic in the literature. The fault diagnosis success of over 95% is achieved. © 2012 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Dissolved gas analysis; Fault diagnosis; Fuzzy logic; Transformer